2011
DOI: 10.1063/1.3658251
|View full text |Cite
|
Sign up to set email alerts
|

The giant electrocaloric effect and high effective cooling power near room temperature for BaTiO3 thick film

Abstract: The electrocaloric effect (ECE) of BaTiO3 multilayer thick film was investigated by direct calorimetric measurement. The ECE increases monotonically with the enhancement of applied field. The maximum ECE occurs above Tc and shifts to higher temperature with increasing applied field. Under an ultrahigh field of 800 kV/cm, it exhibits a giant ECE of ΔT = 7.1 K and ΔS = 10.1 J/kg · K at 80 °C. The ECE heat follows a general power-law relation with the varying rate of applied field within a certain range. A high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(41 citation statements)
references
References 20 publications
1
40
0
Order By: Relevance
“…Different from the standard mode measuring zero-field heat capacity, modified DSC evaluates the heat flow dQ=dE by applying an electric field at a controlled temperature. 26,43,57,84,129,130,132 The electrocaloric heat can be then obtained by Q ¼ Ð E 0 ðdQ=dE 0 ÞdE 0 , which corresponds to the area of the exothermic (endothermic) peak. Therefore, the entropy change can be determined by DS ¼ Q=T.…”
Section: B Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the standard mode measuring zero-field heat capacity, modified DSC evaluates the heat flow dQ=dE by applying an electric field at a controlled temperature. 26,43,57,84,129,130,132 The electrocaloric heat can be then obtained by Q ¼ Ð E 0 ðdQ=dE 0 ÞdE 0 , which corresponds to the area of the exothermic (endothermic) peak. Therefore, the entropy change can be determined by DS ¼ Q=T.…”
Section: B Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…26 Further information about various DSC setups can be found elsewhere (Refs. 26,43,57,84,129,130, and 132 and references therein].…”
Section: B Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Figure 1 compares the ΔT EC values of BaTiO 3 above T C (P r !0) calculated from Eq. (7) [23] with available experimental data [12,16,24,25]. Well-known examples of EC materials driven above the temperature of maximum dielectric permittivity are polyvinylidene fluoride terpolymers and irradiated copolymers, both exhibiting relaxor behaviour.…”
Section: Electrocaloric Effectmentioning
confidence: 99%
“…They observed that-close to the ferroelectric Curie temperature of 222 C-a field change from 77.6 to 29.5 V/μm induced an adiabatic temperature change of 12 K as it was determined from the integrated pyroelectric effect. Recently, another group showed that a lead-free stack of 63 BaTiO 3 thick films provides an EC temperature change of 7.1 K at an applied field of 80 V/ μm [16]. The thickness of the individual layers deposited by tape casting and electrically contacted by inner Ni electrodes amounted to ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation